A sesamoid fracture as a cause of foot pain - Agnieszka Sikora-Wiórkowska; Małgorzata Pucułek; Krzysztof Wiórkowski; Michał Konopelko; Dominik Porada (Kazimierz Wielki University, 2017)
Introduction: A sesamoid bone is an important element of a foot construction. Its function is to properly distribute weigh while walking and to provide correct amortization. The bone is a point which transfers weight in the central part of a foot and that is why it is more prone to damage because of repeated loads. Sesamoid fracture is most often a stress fracture which is common among athletes. Case presentation: 22-year-old patient visited the Orthopedist due to constant pain focused in the plantar range of metatarsophalangeal joint in the left foot with swelling which lasted for 2 months. The pain occurred without any injury and it intensified during physical activity, especially walking. On the basis of performed medical imagining (computerized tomography and magnetic resonance) comminuted lateral sesamoid fracture was diagnosed. Unburdening of foot, cold compresses, physiotherapeutic procedures, kinesiotherapy and intake of non-steroid anti-inflammatory drugs were recommended. Conservative treatment which was used did not provide long-lasting improvement. Surgical interventions were not performed. The patient developed complications due to the abnormal loads of painful foot - locomotion and balance disturbances, pain in the lumbosacral spine. Results: Despite the fact that stress fracture of the sesamoid most often affects athletes who overload forefoot, it can occur also among people with moderate physical activity. During the diagnostic process precise history and magnetic resonance (MR) ought to be taken. The most sensitive and specific imagining exam is MR. At the beginning patient should be treated conservatively. Sesamoidectomy can be considered only when other treatment methods have failed.